2016
DOI: 10.2139/ssrn.2738459
|View full text |Cite
|
Sign up to set email alerts
|

Are the Twin or Triple Deficits Hypotheses Applicable to Post-Communist Countries?

Abstract: This study empirically examines the validity of the twin and triple deficits hypotheses using bootstrap panel Granger causality analysis and an annual panel data set of six post-communist countries (Russia, Poland, Ukraine, Romania, the Czech Republic, and Hungary) from 1994 to 2012. Our findings, based on panel data analysis under cross-sectional dependence and country-specific heterogeneity, support neither the twin deficits hypothesis nor its extended version, the triple deficits hypothesis, for any of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
3
0
3
Order By: Relevance
“…Countering these findings, Domenech et al (2000) tested the triple deficit hypothesis on 18 OECD economies between 1962 and 1994 and found that the cause of the fiscal deficit was not the saving deficits. This is in line with Sen and Kaya (2018) who posited that there was invalidity of the twin or triple deficit hypotheses on six post-communist countries between 1994 and 2012, which agreed with the Ricardian Equivalence Hypothesis and was contrary to conventional approaches implying an absence of the triple deficit hypothesis.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Countering these findings, Domenech et al (2000) tested the triple deficit hypothesis on 18 OECD economies between 1962 and 1994 and found that the cause of the fiscal deficit was not the saving deficits. This is in line with Sen and Kaya (2018) who posited that there was invalidity of the twin or triple deficit hypotheses on six post-communist countries between 1994 and 2012, which agreed with the Ricardian Equivalence Hypothesis and was contrary to conventional approaches implying an absence of the triple deficit hypothesis.…”
Section: Introductionsupporting
confidence: 87%
“…One leading key factor receiving considerable attention is the effect of macroeconomic uncertainty on the fiscal deficit, and current and financial account deficits of balance of payment process. Studies like Kuijs (2006), Bachman (1992), Tang (2014), Sen et al (2014), Sürekçı (2011), Akbas and Lebe (2016), Sen and Kaya (2016), and Shruti et al (2017) are among the few empirical studies that have tested the validity of extension of the twin deficit hypothesis, called the triple deficit hypothesis. Some of these studies are time-series based, while others are both time-series and cross-section based (panel data analysis).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Basit Keynesyen modeldeki açık ekonomideki milli gelir dengesi ikiz ve üçüz açık hipotezlerinin teorik altyapısının başlangıç noktasıdır (Şen & Kaya, 2016). Modelde açık ekonomide t dönemi için GSYİH (1) numaralı denklemde ifade edilmiştir:…”
Section: Teorik Literatürunclassified
“…Tablo 1, ülke grubu özelinde yapılan çalışmaları göstermektedir. Tablo 1'de de görüldüğü üzere, Şen & Kaya (2016), Çoban & Balıkçıoğlu (2016Çoban & Balıkçıoğlu ( ), Özdemir vd. (2014 tarafından yapılan ampirik çalışmalarda üçüz açık hipotezinin geçerli olmadığı sonucuna ulaşılırken, Balan (2016) çalışmasında BRIC ülkelerinde cari açık üzerinde bütçe açığı ve tasarruf açığı etkili olduğu ancak MINT ülkelerinde tasarruf açığı ve cari açık arasında ve tasarruf açığı ile bütçe açığı arasında tek yönlü nedensellik ilişkisine rastlamıştır.…”
Section: Ampirik Literatürunclassified